Hieracia balcanica XVIII. A new species in Hieracium sect. Pannosa (Asteraceae) from the Peloponnese, Greece - Szeląg, Zbigniew (Phytotaxa, 2026)
Hieracium eliae-prophetae, a new, apomictic, tetraploid (x = 9) species combining the morphological features of H. pannosum, H. naegelianum and H. gymnocephalum is described from the Taygetos Mountains in southern Greece. Hieracium eliae-prophetae differs from H. ferdinandi-coburgii in having larger capitula, the presence of numerous stellate hairs on the involucral bracts, often being monocephalous and with a taller stem, narrower cauline leaves, and longer achenes, and corresponds to the morphological formula H. gaudryi–H. graecum.